Analysis of psychologies and behaviors of subway crowds under special events based on survey. Issue 4 (3rd April 2021) - Pan, Fuquan; Zhang, Lixia; Qi, Rongjie; Ma, Changxi; Yang, Jinshun; Tang, Hailiang
Abstract: A questionnaire was designed to investigate the psychologies and behaviors of crowds under special events such as fires, heavy crowd flows, and explosions. Five hundred and fifty-five valid questionnaires were gathered and the information obtained was statistically analyzed. Based on a logistic model, the study analyzed the influence of gender, age, occupation, level of education, and degree of safety knowledge regarding crowd evacuation behavior. The correlation between the characteristics of the crowd and the reactions of the crowd based on evacuation psychologies and behaviors under special events was determined using the chi-square test. The results led to the following conclusions. First, gender, age, level of education, and degree of safety knowledge are significantly correlated with the psychological and behavioral responses of crowds. Second, though most crowds experience fear during a special event due to their lack of experience in coping with such an occurrence, males remain calmer than females during such events. Finally, the greater the degree of safety knowledge possessed by those in the crowd, the more reasonable and efficient the evacuation process is likely to be. This study provides data to support subway evacuation research and it promotes the formulation of reasonable and effective emergency evacuation plans.